Dari Bimbingan ke Pertumbuhan - Sutomo Tatura; Jefit Sumampouw (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2026)
This study aims to analyse the role of pastoral care in shaping the spiritual maturity of congregants, particularly in the context of interpersonal forgiveness within church life. Employing a qualitative approach, data were examined from a range of theological and empirical literature and analysed through descriptive-reflective methods to highlight the dynamics of conflict, inner wounds, and spiritual responses among believers. The findings reveal that pastoral ministry functions as a comprehensive means of faith formation, encompassing teaching, counselling, and both spiritual and emotional support. Forgiveness is understood not merely as an emotional reaction, but as an expression of faith rooted in God’s love through Christ. A lack of willingness to forgive contributes to spiritual tension and prolonged conflict within the fellowship. In this context, pastoral care facilitates relational restoration and the formation of Christian character through contextual and empathetic approaches. Holistic teaching on forgiveness proves to have a significant impact on cultivating spiritually healthy communities. The church plays a crucial role as an agent of healing, embodying God’s love in the lives of its members. Thus, pastoral ministry emerges as a vital instrument in fostering spiritual maturity and unity within the body of Christ